Strong Association between Plasma Dipeptidyl Peptidase-4 Activity and Impaired Cognitive Function in Elderly Population with Normal Glucose Tolerance - Chen, Bo; Zheng, Tianpeng; Qin, Linyuan; Hu, Xueping; Zhang, Xiaoxi; Liu, Yihong; Liu, Hongbo; Qin, Shenghua; Li, Gang; Li, Qinghua (Frontiers in Aging Neuroscience, 2017)
Objective: Inflammation, oxidative stress and decreased glucagon-like peptide-1 (GLP-1) are risk factors for cognitive impairment. Dipeptidyl peptidase-4 (DPP4) was identified as a novel adipokine capable of enhancing these risk factors. Hence, we investigated the relationship between plasma DPP4 activity and impaired cognitive function in elderly Chinese population with normal glucose tolerance. Methods: We performed a cross-sectional study using data from 1229 elderly participants (60 years or older) in Guilin. Plasma DPP4 activity, oxidative stress parameters, fasting active GLP-1, and inflammatory markers were measured in all participants. Impaired cognitive function was diagnosed according to the National Institute on Aging-Alzheimer's Association workgroups criteria. Results: Participants in the upper quartile of plasma DPP4 activity had higher C-reactive protein (CRP), interleukin-6 (IL-6), 8-iso-PGF2a, nitrotyrosine, and lower GLP-1 and Montreal Cognitive Assessment (MoCA) scores compared with those in the lowest quartile (P<0.001). The odds ratios for increased CRP, IL-6, 8-iso-PGF2a, nitrotyrosine and decreased active GLP-1 were higher with increasing DPP4 quartiles after adjustment for confounders (all P<0.001). In the highest DPP4 quartile, impaired cognitive function risk was higher (odds ratio, 2.26; 95% confidence interval, 1.36–3.76) than in the lowest quartile after adjustment for potential confounders. The risk for impaired cognitive function increased more with higher levels of DPP4 activity, nitrotyrosine and 8-iso-PGF2a (P <0.05), but not with higher IL-6, CRP or lower GLP-1. Conclusion: Plasma DPP4 activity is significantly and independently associated with impaired cognitive function, mainly executive, in elderly Chinese population with normal glucose tolerance. The underlying mechanisms for this association may be partly attributed to the effect of DPP4 on oxidative stress. Plasma DPP4 activity might serve as a risk biomarker or therapeutic target for the prevention and treatment of impaired cognitive function.